Analysis of Facebook Professional User Acceptance for Digital Content Monetization with UTAUT 3 - Noli Pitnawati; Dedy Setiawan (Universitas Islam Kuantan Singingi, 2026)
This study aims to analyze the factors influencing the acceptance and use of Facebook Professional as a means of monetizing digital content among the people of Sungai Penuh City. The main problem in this study is the low utilization of this feature despite its significant economic potential. The study used a quantitative approach with the Unified Theory of Acceptance and Use of Technology 3 model expanded with knowledge variables. Data were collected from 195 respondents and analyzed using Structural Equation Modeling-Partial Least Squares. The results showed that perceived usefulness, hedonic motivation, and personal innovation significantly influenced usage intention, while habits, knowledge, and usage intention significantly influenced actual usage behavior. Technical and social factors did not show a dominant influence. This study concluded that personal, psychological, and user experience factors played a greater role in driving the adoption of Facebook Professional than technical factors, so optimizing user education and experience is important in increasing its utilization as a digital economic medium.